2001
DOI: 10.1103/physrevb.64.165403
|View full text |Cite
|
Sign up to set email alerts
|

Near-field optical studies of semicontinuous metal films

Abstract: Local field distributions in random metal-dielectric films near a percolation threshold are experimentally studied using scanning near-field optical microscopy ͑SNOM͒. The surface-plasmon oscillations in such percolation films are localized in small nanometer-scale areas, ''hot spots,'' where the local fields are much larger than the field of an incident electromagnetic wave. The spatial positions of the hot spots vary with the wavelength and polarization of the incident beam. Local near-field spectroscopy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
81
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 59 publications
3
81
0
Order By: Relevance
“…It has been shown that the metallic nanoparticles can effectively confine the optical radiation to 'nanoscale' in the proximity of plasmon resonance; the shape and position of this resonance is controlled by the shape of the nanoparticles (or their clusters) [4][5][6][7][8][9][10][11]. The broadband confinement can be achieved in metal-dielectric films [1,12,13]. Also, the resonant nanoelements can be employed to transmit the optical light at nanoscales [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the metallic nanoparticles can effectively confine the optical radiation to 'nanoscale' in the proximity of plasmon resonance; the shape and position of this resonance is controlled by the shape of the nanoparticles (or their clusters) [4][5][6][7][8][9][10][11]. The broadband confinement can be achieved in metal-dielectric films [1,12,13]. Also, the resonant nanoelements can be employed to transmit the optical light at nanoscales [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…After all, the main requirements for SERS substrates are not only high reproducibility and robust fabrication procedure, but also large-area homogeneity, low cost, and possibility for mass production. One route for the fabrication of large-area structures with "hot spots" could be realized with the semi-continuous metallic films [27][28][29]. These films can be obtained by evaporation of noble metals like gold or silver onto a dielectric or semiconductor substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured gold films have complex behavior as the individual particles have various resonances due to their shape and local neighborhood [1,2]. In recent years electron energy loss spectroscopy (EELS) has been gaining popularity as a technique to map plasmonic resonances in nanostructures [3].…”
Section: Introductionmentioning
confidence: 99%